Perancangan Sistem Informasi Alumni Berbasis Web di Program Studi Sistem Informasi Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi - Sabil Asyrovi; Bastomi Baharsyah; Pol Metra (Jurnal Teknik Informatika dan Teknologi Informasi, 2025)
The alumni information system plays a crucial role in maintaining communication between alumni and educational institutions. Currently, alumni data management at the Information Systems Study Program of UIN Sulthan Thaha Saifuddin Jambi is still conducted manually using Google Forms and WhatsApp groups, leading to difficulties in data recording and updates. Therefore, this research aims to develop a web-based alumni information system to enhance the efficiency of alumni data management, information dissemination, and communication between alumni and the institution. This study employs the Rapid Application Development (RAD) method, which consists of three main stages: requirement planning, system design, and implementation. The system was developed using the CodeIgniter framework and a MySQL database to ensure security and efficiency in alumni data management. The results of testing using the Black Box Testing method indicate that the system functions according to the designed specifications. Additionally, the results of the User Acceptance Testing (UAT) show that 96% the system is well accepted by users as it provides easy access to alumni information, job vacancies, as well as feedback and suggestions. This system is expected to strengthen the relationship between alumni and the institution while offering more effective and structured alumni data management.